EVALUASI PENGGUNAAN OBAT ANTIHIPERTENSI PADA PASIEN GERIATRI RAWAT JALAN DI RSUD DR. A. DADI TJOKRODIPO - Lilik Koernia Wahidah; Novita Tri Wahyuni; Miftahul Choiriah; Hijrah Hijrah (Program Studi Farmasi Universitas Tulang Bawang, 2021)
Hypertension is a condition in which systolic blood pressure â‰¥ 140 mmHg or diastolic blood pressure â‰¥ 90 mmHg. Hypertension is often found in geriatrics that can affect the onslence of heart disease and blood vessels. Increased cases of hypertension, the rational use of drugs by hypertensive patients is one of the important elements in achieving health quality. The purpose of this study is to find out the harsh use of antihypertensive drugs in outpatient geriatric patients at Dr. A. Dadi Tjokrodipo Hospital bandar Lampung. This type of research is non experimental with a descriptive design using retrospective data with purposive sampling methods. The results of the study were based on the pattern of use of antihypertensive with the ATC/DDD method in hypertension patients in Dr. A. Dadi Tjokrodipo Bandar Lampung city is 5331,03 DDD/1000 KPRJ, there are nine types of antihypertensive used, namely amlodipine, lisinopril, candesartan, irbesartan, furosemide, spironolactone, ramipril, bisoprolol and captopril. Antihypertensive in the drug uses segment 90%, namely amlodipine 44.37%, lisinopril 16.88%, candesartan 15.46% and irbesartan 13.65%. The study was based on 100% patient accuracy criteria, 100% indication accuracy, 89.3% drug accuracy and 92% dose accuracy. The conclusion of this study, the pattern of use of antihypertensive widely used is amlodipine amounting to 2365.52 DDD/1000 KPRJ, antihypertensive that enters the drug uses segment 90% namely amlodipine, lisinopril, candesartan and irbesartan.Keywords: Antihypertensive, Geriatrics, Outpatient, Drug Use